2021
DOI: 10.21037/atm-21-2218
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction inhibits renal artery ageing by reducing endothelin-1 expression

Abstract: Background: The renal artery plays a central role in renal perfusion and is critical for proper renal function. Ageing is an independent risk factor for both impaired renal function and vascular disorders, and associated with an increase in the expression of the vasoconstrictor endothelin-1 (ET-1), and caloric restriction (CR) without malnutrition has been shown to be an effective inhibitor of renal dysfunction induced by ageing. The objective of this study was to determine whether CR-mediated alleviation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Furthermore, no downstream effects of IκB and NF-κB were observed. Both IL6 levels, a key inflammatory marker, and the decrease in response to CR observed in the current study are in agreement with results from previous studies [11,33]. Finally, we were not able to detect any changes in markers of senescence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, no downstream effects of IκB and NF-κB were observed. Both IL6 levels, a key inflammatory marker, and the decrease in response to CR observed in the current study are in agreement with results from previous studies [11,33]. Finally, we were not able to detect any changes in markers of senescence.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, there was a decrease in IL6 levels and an increase in NF-κB in females. Previous reports have shown that CR decreases key inflammatory mediators in several tissues, including skeletal muscle (11,30,32,33). It should be noted that most of our results are indirect measures of inflammation.…”
Section: Discussionmentioning
confidence: 51%
“…There are nutrient signalling regulators, which can regulate ageing-related diseases and promote health. Numerous studies show that caloric restriction (CR) prolongs lifespan in laboratory animals [68,69]. Moderate CR can be used to halt the agerelated kidney dysfunction by inhibiting the endothelin-1 (ET-1) expression [68].…”
Section: Senotherapy Agentsmentioning
confidence: 99%
“…Numerous studies show that caloric restriction (CR) prolongs lifespan in laboratory animals [68,69]. Moderate CR can be used to halt the agerelated kidney dysfunction by inhibiting the endothelin-1 (ET-1) expression [68]. In aged mice, physical exercise reduces triacylglycerol and restores plasma lipids homeostasis by regulating lipid metabolism [70].…”
Section: Senotherapy Agentsmentioning
confidence: 99%
“…On the contrary to the results in males, there was a decrease in IL6 and NF-κB protein levels in younger CR treated female rats. Previous reports have shown that CR decreases key inflammatory mediators in several tissues, including skeletal muscle [ 11 , 35 , 37 , 38 ]. It should be noted that most of our results are indirect measures of inflammation.…”
Section: Discussionmentioning
confidence: 99%